Geographical Indications and Transatlantic Trade Negotiations: Different US and EU Perspectives. (27th July 2016) - Mancini, Maria Cecilia; Arfini, Filippo; Veneziani, Mario; Thévenod‐Mottet, Erik
Summary: Intellectual Property Rights (IPRs) are an important issue in the negotiations between the United States (US) and the European Union (EU) for a Transatlantic Trade and Investment Partnership (TTIP) currently underway. However, Geographical Indications (GIs) are one of the most disputed topics because, for decades, the US and the EU have each led one of two seemingly irreconcilable camps on how to address the protection of GIs at the international level. Agreeing on GIs protection in international trade raises important issues related to four dimensions of the GI system, which are likely to become ever more relevant as the TTIP negotiations proceed: i) legal and institutional protection; ii) domestic and international trade; iii) rural/local development and sustainability; and iv) consumers, quality and food safety. Although important, GIs represent only one of the many chapters of the TTIP, and it is in the nature of such agreements that the final text will be the outcome of numerous compromises. To date, the details of the negotiations in the public domain are scant and only in the next few months will we discover whether the protection of GIs in TTIP is a mission possible or will remain an illusory hope. Abstract : Intellectual Property Rights (IPRs) are an important issue in the negotiations between the United States (US) and the European Union (EU) for a Transatlantic Trade and Investment Partnership (TTIP) currently underway. However, Geographical Indications (GIs) are one of the most disputed topics because, for decades, the US and the EU have each led one of two seemingly irreconcilable camps on how to address the protection of GIs at the international level. Agreeing on GIs protection in international trade raises important issues related to four dimensions of the GI system, which are likely to become ever more relevant as the TTIP negotiations proceed: i) legal and institutional protection; ii) domestic and international trade; iii) rural/local development and sustainability; and iv) consumers, quality and food safety. Abstract : Les droits de propriété intellectuelle (DPI) sont une question importante dans les négociations en cours entre les États‐Unis (É‐U) et l'Union européenne (UE) pour établir un Partenariat transatlantique de commerce et d'investissement (TTIP). Les Indications géographiques (IG) sont l'un des sujets les plus controversés car depuis des décennies, les É‐U et l'UE ont mené deux camps apparemment irréconciliables sur la façon de protéger les IG au niveau international. S'accorder sur la protection des IG dans le commerce international soulève des questions importantes liées à quatre dimensions du système d'IG, qui deviendront probablement encore plus pertinentes à mesure de l'avancement des négociations : i) la protection institutionnelle et juridique ; ii) le commerce interne et international ; iii) le développement rural/local et la durabilité ; et iv) les consommateurs, la qualité et l'innocuité des aliments. Les IG sont importantes mais elles ne représentent que l'un des nombreux chapitres du TTIP. Conformément à la nature de tels accords, le texte du TTIP résultera de multiples compromis. À ce jour, les détails sur ses négociations accessibles au public sont maigres et c'est seulement dans les quelques mois à venir que nous découvrirons si la protection des IG dans le TTIP est une mission possible ou si elle restera un espoir illusoire. Abstract : Das Thema geistige Eigentumsrechte stellt einen wichtigen Punkt in den Verhandlungen zwischen den Vereinigten Staaten (USA) und der Europäischen Union (EU) für das geplante Transatlantische Freihandelsabkommen dar. Zu den strittigsten Punkten gehören jedoch die geografischen Angaben, da die USA und die EU seit Jahrzehnten zwei anscheinend nicht miteinander zu vereinbarende Standpunkte vertreten, wie der Schutz geografischer Angaben auf internationaler Ebene zu behandeln ist. Mit einem Freihandelsabkommen, das den Schutz geografischer Angaben vorsieht, würden wichtige Fragen im Zusammenhang mit vier Aspekten für die Regelung für geografische Angaben aufgeworfen, die mit fortschreitenden Verhandlungen über das Freihandelsabkommen an Bedeutung zunehmen dürften: (1) Rechtlicher und institutioneller Schutz; (2) Binnen‐ und Welthandel; (3) ländliche/regionale Entwicklung und Nachhaltigkeit; (4) Verbraucher, Qualität und Nahrungsmittelsicherheit. Geografische Angaben stellen zwar einen wichtigen Punkt, aber trotzdem nur einen Teil des Transatlantischen Freihandelsabkommens dar, und naturgemäß ist die endgültige Version solcher Abkommen das Ergebnis zahlreicher Kompromisse. In der Öffentlichkeit ist bislang nur wenig über die Einzelheiten der Verhandlungen bekannt, und nur die kommenden Monate werden zeigen, ob der Schutz geografischer Angaben realisierbar ist oder ein Wunschbild bleiben wird.